Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Kuhns, Victoria L. Halperin; et al. (Nature Communications, 2021)
Serum urate concentration can be studied in large datasets to find genetic and epigenetic loci that may be related to cardiometabolic traits. Here the authors identify and replicate 100 urate-associated CpGs, which provide insights into urate GWAS loci and shared CpGs of urate and cardiometabolic traits.
CRIS-Team WoS Importer:2021-12-17